[C i](1-0) and [C i](2-1) in resolved local galaxies - Crocker, Alison F.; Pellegrini, Eric William; Schinnerer, Eva (The astrophysical journal, 2019)
We present resolved [C i] line intensities of 18 nearby galaxies observed with the SPIRE FTS spectrometer on the Herschel Space Observatory. We use these data along with resolved CO line intensities from J up = 1 to 7 to interpret what phase of the interstellar medium the [C i] lines trace within typical local galaxies. A tight, linear relation is found between the intensities of the CO(4-3) and [C i](2-1) lines; we hypothesize this is due to the similar upper level temperature of these two lines. We modeled the [C i] and CO line emission using large-velocity gradient models combined with an empirical template. According to this modeling, the [C i](1-0) line is clearly dominated by the low-excitation component. We determine [C i] to molecular mass conversion factors for both the [C i](1-0) and [C i](2-1) lines, with mean values of α [C i](1−0) = 7.3 M ⊙ K−1 km−1 s pc−2 and α [C i](2−1) = 34 M ⊙ K−1 km−1 s pc−2 with logarithmic root-mean-square spreads of 0.20 and 0.32 dex, respectively. The similar spread of to (derived using the CO(2-1) line) suggests that [C i](1-0) may be just as good a tracer of cold molecular gas as CO(2-1) in galaxies of this type. On the other hand, the wider spread of α [C i](2−1) and the tight relation found between [C i](2-1) and CO(4-3) suggest that much of the [C i](2-1) emission may originate in warmer molecular gas.